Dehalogenation of Chlorinated Hydroxybiphenyls by Fungal Laccase - Schultz, Asgard (American Society for Microbiology, 2001)
We have investigated the transformation of chlorinated hydroxybiphenyls by laccase produced by Pycnoporus cinnabarinus. The compounds used were transformed to sparingly water-soluble colored precipitates which were identified by gas chromatography-mass spectrometry as oligomerization products of the chlorinated hydroxybiphenyls. During oligomerization of 2-hydroxy-5-chlorobiphenyl and 3-chloro-4-hydroxybiphenyl, dechlorinated C—C-linked dimers were formed, demonstrating the dehalogenation ability of laccase. In addition to these nonhalogenated dimers, both monohalogenated and dihalogenated dimers were identified.